2012
DOI: 10.1073/pnas.1121601109
|View full text |Cite|
|
Sign up to set email alerts
|

Antiproliferative small-molecule inhibitors of transcription factor LSF reveal oncogene addiction to LSF in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the fifth most common cancer worldwide. Despite the prevalence of HCC, there is no effective, systemic treatment. The transcription factor LSF is a promising protein target for chemotherapy; it is highly expressed in HCC patient samples and cell lines, and promotes oncogenesis in rodent xenograft models of HCC. Here, we identify small molecules that effectively inhibit LSF cellular activity. The lead compound, factor quinolinone inhibitor 1 (FQI1), inhibits LSF DNA-binding act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
67
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(76 citation statements)
references
References 34 publications
9
67
0
Order By: Relevance
“…In addition to TS, LSF transcribes several genes associated with aggressive cancers, including osteopontin (OPN), MMP9, MET, and complement factor H (CFH) (Yoo et al, 2011b). A high-throughput screen identified factor quinolinone inhibitor 1 (FQI1) as an LSF DNA binding inhibitor that induces apoptosis and inhibits proliferation of HCC cells (Grant et al, 2012). Because specific inhibitors to target AEG-1/MTDH/LYRIC have not been identified, inhibiting AEG-1/MTDH/LYRIC downstream effector LSF may provide a new strategy to treat HCC.…”
Section: Aeg-1/mtdh/lyric Downstream Genes Identified By Microarraymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to TS, LSF transcribes several genes associated with aggressive cancers, including osteopontin (OPN), MMP9, MET, and complement factor H (CFH) (Yoo et al, 2011b). A high-throughput screen identified factor quinolinone inhibitor 1 (FQI1) as an LSF DNA binding inhibitor that induces apoptosis and inhibits proliferation of HCC cells (Grant et al, 2012). Because specific inhibitors to target AEG-1/MTDH/LYRIC have not been identified, inhibiting AEG-1/MTDH/LYRIC downstream effector LSF may provide a new strategy to treat HCC.…”
Section: Aeg-1/mtdh/lyric Downstream Genes Identified By Microarraymentioning
confidence: 99%
“…Because specific inhibitors to target AEG-1/MTDH/LYRIC have not been identified, inhibiting AEG-1/MTDH/LYRIC downstream effector LSF may provide a new strategy to treat HCC. Indeed, LSF may very well represent an “Achilles heel” for HCC given the addiction to LSF for survival (Grant et al, 2012). …”
Section: Aeg-1/mtdh/lyric Downstream Genes Identified By Microarraymentioning
confidence: 99%
“…In all cases, inhibition of tumor growth occurred in the absence of toxicity, as assessed by liver injury markers, histopathology of tissues with rapid cell turnover, or blood cell counts (18). These results suggested that hepatocellular carcinoma cells are oncogene addicted to LSF (14,19).…”
Section: Introductionmentioning
confidence: 87%
“…A family of small molecule inhibitors of LSF, Factor Quinolinone Inhibitors (FQIs), was identified that inhibits the DNA binding and transcription activity of LSF, but not that of transcription factors from multiple other structural classes (14). Activity of p53, the closest structural relative of the LSF family (15,16), was also not inhibited by FQIs.…”
Section: Introductionmentioning
confidence: 99%
“…A high-throughput screening identified small-molecule inhibitors of LSF DNA binding and the prototype of these molecules, Factor quinolinone inhibitor 1 (FQI1), profoundly inhibited cell viability and induced apoptosis in human HCC cells without exerting harmful effects to normal immortal human hepatocytes and primary mouse hepatocytes (Grant et al, 2012). In nude mice xenograft studies, FQI1 markedly inhibited growth of human HCC xenografts as well as angiogenesis without exerting any toxicity.…”
Section: Aeg-1/mtdh/lyric Downstream Genesmentioning
confidence: 99%